HIGH PRESSURE ELASTIC ANISOTROPY OF MGSIO3 PEROVSKITE AND GEOPHYSICAL IMPLICATIONS - Wentzcovitch R.M.; Karki B.B.; Karato S.; Da Silva C.R.S. (My University, 1998)
Using plane wave pseudopotential method within the local density approximation (LDA), we calculate single-crystal elastic constants (cij) of orthorhombic MgSiO3 perovskite, generally accepted to be the major component of the lower mantle, as a function of pressure up to 150 GPa. Our results are in excellent agreement with experimental data at zero pressure and compare favorably with other pseudopotential predictions over the pressure regime studied. Here we use our elastic constants to calculate anisotropy of seismic wave velocities as a function of pressure (depth). MgSiO3 perovskite is shown to be highly anisotropic in all portions of the lower mantle and the nature of anisotropy changes significantly with depth. The absence of significant seismic anisotropy in most of the lower mantle suggests that MgSiO3 perovskite assumes nearly random orientation in most of this region. Anisotropy at the topmost lower mantle suggested by some studies can be attributed to the preferred orientation of perovskite. However, anisotropy in the D layer is difficult to be attributed to preferred orientation of perovskite. Some other mechanisms including the presence of the aligned melt pockets and/or lattice preferred orientation of magnesiowustite are needed.
Keywords: HIGH PRESSURE; ELASTICITY; ANISOTROPY; LOWER MANTLE